A methodology for creating feeding routes in mass transit systems - Ospina-Toro, Daniela; Toro-Ocampo, Eliana Mirledy; Gallego-Rendón, Ramón Alfonso (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This paper proposes a methodology to identify feeding routes for areas disconnected to the Mass Transit System (MTS), in order to propose an alternative solution to the deficit in the number of carried passengers. The proposed methodology consists of two steps: (1) structuring scenarios for areas disconnected from the transport system, and (2) combining heuristic and exact techniques to solve the feeding routes problem. The methodology considers among its restrictions the path length and the passenger vehicle capacity. To model the problem, a comparison with the Location Routing Problem (LRP), which is usually applied to freight transport problems, was established. The proposed methodology is a math-heuristic that combines the Lin-Kernighan-Helsgaun algorithm (LKH), and the Clark and Wright’s Savings heuristic with the Branch-and-Cut exact algorithm, which is applied into a Mixed Integer Linear Programming model (MILP), also known as a Set Partitioning model (SP) for LRP. This methodological approach is validated with real instances in the massive transport system of Pereira (Megabús), considering some areas disconnected from the Central-Occidental Metropolitan Area System (AMCO) of Pereira, located in the Colombia's Coffee Axis.